Are they guilty of their parental behavior? Parenting forms constructed in termination of parental rights court cases. (July 2016) - Ben-David, Vered
The study examines forms of parenting constructed in Israeli termination of parental rights (TPR) cases, and the processes involved in their construction, based on a qualitative thematic analysis of 130 TPR cases. The study hypothesized that, due to lack of clearly-defined evaluation criteria, judges and professionals engage in social constructions of reality processes related to the child–parent relationship. The analysis indicated that, through constructions of non-normative parenting, biological parents are depicted, in court, not only as dysfunctional and parentally unfit but also as "guilty." Four categories of such parenting were identified: impaired, "failed, " dangerous and harmful. The perception of guilt resulted from the courts' attribution of parental behavior to pathological psychological factors, while ignoring contextual factors such as poverty and stress. The study discusses how negative views of parenting impact on legal decisions aimed at serving the child's best interests and consequent implications for social work and legal practices.